A critical review to traumatic brain injury clinical practice guidelines. Issue 9 (March 2019) - Di, Bao-shan; Wei, Min; Ma, Wen-juan; Zhang, Qi; Lu, An-qing; Wang, Hu; Niu, Yang; Cao, Nong; Guo, Tian-kang
Abstract : Abstract: The aim of this study was to assess the quality of clinical practice guidelines of traumatic brain injury (TBI) and investigate the evidence grading systems. A systematic search of relevant guideline websites and literature databases (including PubMed, NGC, SIGN, NICE, GIN, and Google) was undertaken from inception to May 2018 to identify and select TBI guidelines. Four independent reviewers assessed the eligible guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument. The degree of agreement was evaluated with intraclass correlation coefficient (ICC). From 1802 records retrieved, 12 TBI guidelines were included. The mean scores for each AGREE II domain were as follows: scope and purpose (mean ± SD= 74.2 ± 9.09); stakeholder involvement (mean± SD= 54.6 ± 11.6); rigor of development (mean ± SD=70.1 ± 13.6); clarity and presentation (mean ± SD=78.4 ± 11.5); applicability (mean ± SD= 60.5 ± 13.6); and editorial independence (mean ± SD=61.7 ± 14.8). Ten guidelines were rated as "recommended." The ICC values ranged from 0.73 to 0.95. Seven grading systems were used by TBI guidelines to rate the level of evidence and the strength of recommendation. Most TBI guidelines got a high-quality rating, whereas a standardized grading system should be adopted to provide clear information about the level of evidence and strength of recommendation in TBI guidelines.